2016
DOI: 10.1371/journal.pntd.0005059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Reference Center on Leprosy Control under a Decentralized Public Health Care Policy in Brazil

Abstract: Reorientation of the public health policies in Brazil over the last 20 years in association with a stable rate of new-case detection prompted the establishment of a decentralized leprosy control strategy. The aim was to move from a vertical model associated with general dermatological services to one in which the diagnosis and treatment of the disease would be integrated into the primary care level of the national health care facilities. Once patients demand for leprosy reference centers began to be affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
1
27
0
5
Order By: Relevance
“…This study identified that these areas have a higher proportion of patients with advanced forms of leprosy, vis a vis MB leprosy and individuals with grade 2 disability, likely reflecting a late diagnosis and barriers to access health services. Brazil, Bangladesh and India have long reported the well‐established relationship between poverty and the occurrence of advanced forms of leprosy and that patients in areas with good primary healthcare services are diagnosed earlier . Socio‐economic differences influence not only access, but also the quality and utilization of health services …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified that these areas have a higher proportion of patients with advanced forms of leprosy, vis a vis MB leprosy and individuals with grade 2 disability, likely reflecting a late diagnosis and barriers to access health services. Brazil, Bangladesh and India have long reported the well‐established relationship between poverty and the occurrence of advanced forms of leprosy and that patients in areas with good primary healthcare services are diagnosed earlier . Socio‐economic differences influence not only access, but also the quality and utilization of health services …”
Section: Discussionmentioning
confidence: 99%
“…Brazil, 5,17,22,26,27 Bangladesh 16 and India [28][29][30] have long reported the well-established relationship between poverty and the occurrence of advanced forms of leprosy and that patients in areas with good primary healthcare services are diagnosed earlier. 22,31,32 Socioeconomic differences influence not only access, but also the quality and utilization of health services. 6 Our findings also highlight that leprosy has not declined over time in municipalities with high social vulnerability, despite major efforts to eradicate leprosy with active case detection and contact tracing.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, socioeconomic and environmental conditions are linked to the permanence of the leprosy transmission chain. Thus, the presence of geographic areas with high social deprivation and which also have high leprosy detection coefficients explains the influence of the fragile socioeconomic conditions of the population on the maintenance of the Mycobacterium leprae transmission chain [38][39][40][41][42] . As a result of all the investigations conducted here, the central element chosen for the definition of priority areas was high/very high social deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for these findings may be based on the expansion of the primary health care network all over Brazil in recent years. 9,20,21 A study conducted by Nery et al 20 which analyzed 1,358 Brazilian municipalities, showed that the then Family Health Program (FHP) -now referred to as the Family Health Strategy (FHS) -made progress in increasing the detection of new cases of leprosy. Moreover, the existence of decentralized health centers was also associated with increased detection of the disease.…”
Section: Spatialization Of Leprosy In Bahiamentioning
confidence: 99%